2014
DOI: 10.1177/1087054714527790
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Effect of Bilingualism and ADHD on Executive Functions

Abstract: Bilingualism might prove to be an added burden for adults with ADHD, leading to reduced EF abilities. Alternatively, the current findings might be ascribed to over- or under-diagnosis of ADHD due to cultural differences between groups. These issues should be pursued in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 55 publications
0
54
1
Order By: Relevance
“…However, the global bilingual advantage (especially with regard to EF) does not persist among those with certain impairments or disorders e.g., ADHD (e.g., Boonstra, Oosterlaan, Sergeant & Buitelaar, ). In the Mor, Yitzhaki‐Amsalem and Prior () study, the lowest outcome performances for EF were observed among bilinguals with ADHD relative to monolinguals with or without ADHD and bilinguals without ADHD. These authors concluded that the combined effect of bilingualism and ADHD cannot improve EF deficits.…”
Section: Introductionmentioning
confidence: 88%
“…However, the global bilingual advantage (especially with regard to EF) does not persist among those with certain impairments or disorders e.g., ADHD (e.g., Boonstra, Oosterlaan, Sergeant & Buitelaar, ). In the Mor, Yitzhaki‐Amsalem and Prior () study, the lowest outcome performances for EF were observed among bilinguals with ADHD relative to monolinguals with or without ADHD and bilinguals without ADHD. These authors concluded that the combined effect of bilingualism and ADHD cannot improve EF deficits.…”
Section: Introductionmentioning
confidence: 88%
“…The Simon effect is calculated by subtracting the average reaction time or error rate on the congruent trials from the average reaction time or error rate on the incongruent trials. Some studies have shown a bilingual advantage in this or a similar task Martin-Rhee & Bialystok, 2008;Morales et al, 2013), but even more studies have yielded null results (Ansaldo et al, 2015;von Bastian et al, 2016;De Bruin et al, 2015;Gathercole et al, 2014;Kousaie & Phillips, 2012;Kousaie et al, 2014;Mor et al, 2014;Morton & Harper, 2007;Namazi & Thordardottir, 2010;Paap & Greenberg, 2013;.…”
Section: Tasks and Questionnairesmentioning
confidence: 99%
“…Indeed, there are studies indicating that compared to monolinguals, early bilinguals show an advantage on executive functions, thought to stem from life-long bilingual language use (e.g. Bak, Nissan, Allerhand, & Deary, 2014;Bialystok, 1999;Bialystok, Craik, Klein, & Viswanathan, 2004;Bialystok, Craik, & Luk, 2008;Bialystok, Craik, & Ryan, 2006;Bialystok & Majumder, 1998;Bialystok & Martin, 2004;Bialystok & Viswanathan, 2009;Calvo Gathercole et al, 2014;Hilchey & Klein, 2011;Kousaie & Phillips, 2012;Kousaie, Sheppard, Lemieux, Monetta, & Taler, 2014;Mor, Yitzhaki-Amsalem, & Prior, 2014;Paap & Greenberg, 2013;Ratiu & Azuma, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies to date have used a categorical approach to address the potential interaction between bilingualism and attention ability on EF in an adult population. In the first, Mor, Yitzhaki‐Amsalem and Prior () administered EF tasks to young adults from a university population who had been diagnosed with clinical ADHD or not and whom they classified as monolingual or bilingual. Their results showed the poorest performance among those who were classified as bilingual with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…In the stop signal task, in contrast, the bilinguals with ADHD were significantly more impaired than were participants in the other groups, consistent with the findings by Mor et al . () for trilinguals. Thus, the essential questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%